South Asia, growth and regional integration - Ahmed, Sadiq; Ghani, Ejaz (Macmillan, 2007)
Contributed articles presented at the first SAARC Business Conclave held in November 2005 at New Delhi jointly organized by World Bank, SAARC and SCCI.